Pleural Fluid Glucose – Routine but Vital Biochemical Parameter for Differential Diagnosis of Effusions - Ashish Jadhav; Anuradha Jain; ArvindYadav; Poonam Kamble (Walawalkar International Medical Journal, 2017)
Biochemical parameters in pleural fluid are usually done to identify the cause of pleural effusion. Differentiating the effusion into either transudative or exudative is a logical first step, with further investigations dictated by the clinical features and these results. Light’s criteria and other biochemical parameters help to obtain a result for differentiating the effusion. Not a single laboratory value will draw a conclusion of being the effusion as transudative or exudative, hence combining number of biochemical test will help to obtain a definitive result. Pleural glucose measurement is routine and age old parameter used to identify cause of pleural effusion. In this review we tried to evaluate the usefulness of pleural glucose in effusion. In country like India, where all routine and specialized biochemical parameters may not be available for identifying the specific cause of effusion, the estimation of pleural glucose may help to draw an initial approach for classifying an effusion.